Comparing effects of two higher intensity feedback interventions with simple feedback on improving staff communication in nursing homes—the INFORM cluster-randomized controlled trial - Hoben, Matthias (Implement Sci, 2020)
BACKGROUND: Effective communication among interdisciplinary healthcare teams is essential for quality healthcare, especially in nursing homes (NHs). Care aides provide most direct care in NHs, yet are rarely included in formal communications about resident care (e.g., change of shift reports, family conferences). Audit and feedback is a potentially effective improvement intervention. This study compares the effect of simple and two higher intensity levels of feedback based on goal-setting theory on improving formal staff communication in NHs. METHODS: This pragmatic three-arm parallel cluster-randomized controlled trial included NHs participating in TREC (translating research in elder care) across the Canadian provinces of Alberta and British Columbia. Facilities with at least one care unit with 10 or more care aide responses on the TREC baseline survey were eligible. At baseline, 4641 care aides and 1693 nurses cared for 8766 residents in 67 eligible NHs. NHs were randomly allocated to a simple (control) group (22 homes, 60 care units) or one of two higher intensity feedback intervention groups (based on goal-setting theory): basic assisted feedback (22 homes, 69 care units) and enhanced assisted feedback 2 (23 homes, 72 care units). Our primary outcome was the amount of formal communication about resident care that involved care aides, measured by the Alberta Context Tool and presented as adjusted mean differences [95% confidence interval] between study arms at 12-month follow-up. RESULTS: Baseline and follow-up data were available for 20 homes (57 care units, 751 care aides, 2428 residents) in the control group, 19 homes (61 care units, 836 care aides, 2387 residents) in the basic group, and 14 homes (45 care units, 615 care aides, 1584 residents) in the enhanced group. Compared to simple feedback, care aide involvement in formal communications at follow-up was 0.17 points higher in both the basic ([0.03; 0.32], p = 0.021) and enhanced groups ([0.01; 0.33], p = 0.035). We found no difference in this outcome between the two higher intensity groups. CONCLUSIONS: Theoretically informed feedback was superior to simple feedback in improving care aides’ involvement in formal communications about resident care. This underlines that prior estimates for efficacy of audit and feedback may be constrained by the type of feedback intervention tested. TRIAL REGISTRATION: ClinicalTrials.gov (NCT02695836), registered on March 1, 2016